Large‐area high quality PtSe2 thin film with versatile polarity. Issue 2 (29th May 2019) - Jiang, Wei; Wang, Xudong; Chen, Yan; Wu, Guangjian; Ba, Kun; Xuan, Ningning; Sun, Yangye; Gong, Peng; Bao, Jingxian; Shen, Hong; Lin, Tie; Meng, Xiangjian; et al.
Abstract: Two‐dimensional (2D) materials have attracted increasing attention for their outstanding structural and electrical properties. However, for mass‐production of field effect transistors (FETs) and potential applications in integrated circuits, large‐area and uniform 2D thin films with high mobility, large on‐off ratio, and desired polarity are needed to synthesize firstly. Here, a transfer‐free growth method for platinum diselenide (PtSe2 ) films has been developed. The PtSe2 films have been synthesized with various thicknesses in centimeter‐sized scale. Typical FET made from a few layer PtSe2 show p‐type unipolar, with a high field‐effect hole mobility of 6.2 cm 2 V −1 s −1 and an on‐off ratio of 5 × 10 3 . The versatile semimetal‐unipolar‐ambipolar transition in synthesized PtSe2 films is also firstly observed as the thickness thinning. This work realizes the large‐scale preparation of PtSe2 with prominent electrical properties and provides a new strategy for polarity's modulation. Abstract : A transfer‐free growth method is preformed to synthesize large‐area platinum diselenide (PtSe2 ) films with prominent mobility and on‐off ratio. The versatile semimetal‐unipolar‐ambipolar transition in those uniform PtSe2 films is perfectly exhibited and explained by the influence of film thickness and Se vacancy in detail.